Emporiatric enteritis: lessons learned from U.S. students in Mexico. - Dupont, H. L. (American Clinical and Climatological Association, 1986)
In the studies reported, evidence has been presented that U.S. students traveling to Mexico represent a model for the study of travelers' diarrhea. The incidence of illness acquisition approximates that published in other studies of travelers. Natural immunity was shown to develop as students remained in Mexico presumably through repeated exposure to prevalent agents, particularly ETEC. ETEC, shigella strains and no detectable agent represented the largest groups when etiologic assessment was made. Food probably served as the important source of diarrhea particularly that due to ETEC and shigella strains. The level of bacteria isolated from food suggested that organism replication occurred due to improper temperature storage rather than to heavy initial contamination. The location of food consumption was related to degree of risk: self preparation was the safest, eating in Mexican homes the least safe and consumption of food in public restaurants was intermediate in risk. Water probably played a role in the transmission of viral infection. The risk of water contamination appeared to be highest during the rainy seasons. Finally, the antimicrobial agents TMP/SMX and TMP alone were shown to effectively prevent and treat this form of travelers' diarrhea.